Literatura moral e discursos jurídicos : em torno dos privilégios femininos no século XVI em Portugal - Fernandes, Maria de Lurdes Correia (2000)
This article offers a rereading of Dos privilégios e preerogativas que o género feminino tem por direito comum e ordenações do Reino mais que o género masculino by Rui Gonçalves, printed in Lisbon in 1557, which takes into account the historical and cultural context of the work. The focus is both on some vectors of moral literature with links to a politicai framework and on certain aspects of the laws which allegedly were aimed at the protection of some "privileges" of women. The limits of the concept of "privilege" as applied to women are discussed, as well as the possible meanings attached to the compiling of those laws and their links to models and practices of "feminine" behaviour which influenced some of the main orientations of behavioural morais in the 16lh Century.